Peran Regulasi Diri Islami dan Karakteristik Pekerjaan Terhadap Komitmen Organisasional Pada Karyawan Organisasi Syariah - Ugung Dwi Ario Wibowo (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2013)
Sharia organization founded in order to realize fallah (the common good), had a classic probems that is employees turnover problem. By that case, researcher interested in studying the role of islamic self-regulation and job characteristic on organizational commitment to the employees of sharia organization. Quantitative research study was classified based on the type of data and data analysis procedures. The independent variables in this study are: islamic self-regulation and job characteristic, while the dependent variable in this study is: organizational commitment. The subjects in this study were 44 employees in BMT. Hypothesis testing with multiple regression analysis, which data analysis calculate using SPSS For Windows Release 17.00 programme. Conclusions from this research are: (1) Islamic self-regulation had significant effect on organizational commitment, (2) job characteristic had significant effect on organizational commitment, and (3) Islamic self-regulation and job characteristic had simultant significant effect on organizational commitment.Keywords: islamic self-regulation, job characteristic, organizational commitment, sharia organization